Doença pulmonar obstrutiva crônica - De Godoy, I.; De Castro Silva, M. H. (My University, 1991)
Chronic obstructive pulmonary disease (COPD) is an extremely common disorder that all primary care physicians should be able to manage. In this review we will define the entities incorporated in COPD and will present various aspects of the diagnoses and treatment. We could not cover every aspect of this broad topic even providing a detailed review of those areas but some facets of therapy like smoking cessation, drug therapy, oxygen therapy, nutrition, and respiratory rehabilitation will be described.
Chronic obstructive pulmonary disease
Keywords: almitrine dimesilate; aminophylline; amoxicillin; antiinfective agent; beclometasone; beta adrenergic receptor stimulating agent; betamethasone; cephalosporin derivative; cholinergic receptor blocking agent; cimetidine; ciprofloxacin; contraceptive agent; corticosteroid; cotrimoxazole; dexamethasone; diuretic agent; erythromycin; expectorant agent; fenoterol; hydrocortisone; ipratropium bromide; macrolide; methylprednisolone; mucolytic agent; oxygen; phenytoin; prednisone; rifampicin; salbutamol; sulfamethoxazole; terbutaline; theophylline derivative; trimethoprim; vaccine; cardiovascular disease; central nervous system function; chronic bronchitis; chronic obstructive lung disease; digestive system function disorder; drug half life; drug mixture; emphysema; human; inhalational drug administration; intramuscular drug administration; nutrition; oral drug administration; review